Development of Story Jumper-Based Interactive Illustrated Storybooks to Improve Kindergarten Children’s Science Skills - Lilis Sumanti; Yaswinda Yaswinda; Setiyo Utoyo; Nurhafizah Nurhafizah (Postgraduate, University of Mataram, 2026)
The limited availability of interactive learning media has contributed to the low development of early childhood science skills in kindergarten learning. This study aimed to develop and evaluate an interactive illustrated storybook based on the Story Jumper platform to improve science skills among children aged 5–6 years. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The study involved two expert validators, one media expert and one material expert, while the field testing was conducted with 20 kindergarten children in Group B at TK Negeri Pembina Ranah Batahan, West Pasaman, Indonesia. Data were collected through validation sheets, practicality questionnaires, observation sheets, and pretest–posttest assessments. The findings indicated that the developed media achieved a very valid category, with validation scores of 91.6% from material experts and 88.8% from media experts. The practicality assessment by teachers reached 94.44%, indicating that the media was highly practical and easy to implement in classroom activities. Furthermore, the effectiveness test showed an increase in children’s science skills, reflected by an N-Gain score of 0.6656 in the moderate-to-high category. The study demonstrates that the Story Jumper–based illustrated storybook can serve as an innovative and effective digital learning medium to support the development of early childhood science skills through interactive and contextual learning experiences